Comparison of haematopoietic stem cell engraftment through the retro-orbital venous sinus and the lateral vein: alternative routes for bone marrow transplantation in mice. (April 2015) - Leon-Rico, D; Fernández-García, M; Aldea, M; Sánchez, R; Peces-Barba, M; Martinez-Palacio, J; Yáñez, RM; Almarza, E
Bone marrow transplantation in mice is performed by intravenous administration of haematopoietic repopulating cells, usually via the lateral tail vein. This technique can be technically challenging to carry out and may cause distress to the mice. The retro-orbital sinus is a large area where there is a confluence of several vessels that provides an alternative route for intravenous access. Retro-orbital injection, although aesthetically unpleasant, can be performed rapidly without requiring mechanical restriction or heat-induced vasodilation. In addition, this technique can be easily learned by novice manipulators. This route of administration has been reported for use in bone marrow transplantation but there is no comparison of retro-orbital and tail vein injections reported for this specific purpose, although both routes have been compared for many other applications. Here, we provide for the first time a comprehensive comparison between tail vein and retro-orbital injections for two different bone marrow transplant scenarios in P3B and B6D2F1 mice. In both cases, no significant differences regarding donor engraftment were observed between mice transplanted using each of the techniques. Haematological counts and leukocyte subpopulation distribution were practically identical between both animal groups. Moreover, donor engraftment levels were less homogenous when cells were transplanted by tail vein injection, probably due to a higher risk of failure associated with this technique. All these data suggest that retro-orbital injection is a compelling alternative to conventional tail vein injection for bone marrow transplant in mice, providing similar and more homogenous haematopoietic reconstitution.